Memórias, história e representações das escolas rurais do município de Uberlândia - MG na Era Vargas (1930-1945). - Tannús, Márcia Cristina (2017)
This research is part of the History of Education and has as its theme the memories and representations of the rural school built in the municipality of Uberlândia during the Vargas Era (1930-1945). The objective of this study was to understand how the rural school education in Uberlândia appropriated through the use of images and symbols of a broader national project that intended to use the instruction to form "new citizens". The research hypothesis was that the representations made about rural education in the Vargas Era demanded a considerable effort from the local authorities using rules, hygienic standards and symbols to adapt the school organization that already existed in the city of Uberlândia / MG to the national purpose of the time. The methodological procedures of this research included selection, critical reading and analysis of sources deposited in the Municipal Public Archive of the city, such as: photographs, laws, accounting reports, school meetings minutes, newspaper articles, point books, miscellaneous correspondences and official speeches . The categories chosen for analysis in this study were: working conditions, subjects involved in the process and symbols present in the daily school life. The results to which we arrived allow us to affirm that in relation to the organization and functioning of rural schools the existence of precarious conditions for the execution of limited teaching work adequate to current norms was configured in the school daily life of the municipality. With regard to the use of symbols and images, it was possible to understand that they were essential for the construction of the patriotic and harmonic representations associated with the school, desired by the governments of the period.